An approach to Social Work from the perspective of Positive Psychology - Jiménez Rodríguez, Virginia; Alvarado Izquierdo, Jeús María; Puente Ferreras, Aníbal (Cuadernos de Trabajo Social, 2013)
Positive psychology is a social science of relatively recent development that analyzes the bases of psychological wellbeing from the strengths and virtues of each individual and their potential to influence others to achieve the fullness and personal development. In the context of Positive Psychology VIA-Is test was applied to 186 first grade of Social Work students at the University Complutense of Madrid during 2011-2012. The aim of this investigation was to establish the profile of virtues and strengths which the student considers the key for the future performance as a social worker. The virtues of Humanity and Fairness were considered the most relevant by the students, as expected, because of these virtues are essential when they come to influence the will of others, respecting the individuality of user to a state of wellbeing (Peterson &Seligman, 2004).
Keywords: Positive Psychology; strengths; virtues; social worker; VIA-IS